Women's control over productive assets: role of credit based development interventions - Huda, Samiha; Mahmud, Simeen (BRAC, 2019)
This paper examines the degree to which participation in BRAC's development intereventions has any impact on women's ownership and control over assets. Information was collected under BRAGICDDR,B joint research project at Matlab during April-August 1995 through structured interview. In addition to socio-economic and demographic characteristics, information regarding ownership and control over assets was elicited from 2295 currently married women between 15-55 years of age of whom 22% were BRAC members. Bivariate distribution comparing members and non-members in terms of asset ownership and control were assessed through use of indices. Women's assets were categorized into big and small according to their relative value. findings reveal that women's ownership and control over big assets increased with age. Currently married women tend to own more big assets and have greater control over those, but levels of schooling did not appear to effect either ownership or control. Women's ownership and control over small assets were not found to have any assocaition with women's age or household head's occopational status. When compared with eligible non-members, BRAC members appeared to have greater ownership · and control over assets, (both big and small). However, no difference was seen amongst members in terms of ownership and control over assets when BRAC membership was categorized according to duration, intensity and type.